Algılanan İslamofobi’ Ölçeğinin Norveç’te Yaşayan Cami ve Dini Dernek Üyeleri Üzerinde Uygulanması/The Implementation of the “Perceived Islamophobia Scale” on The Mosque and Religious Association Members Living in Norway - Musa Gelici (Oksident, 2025)
This study focuses on the perceptions of Islamophobia among Muslims residing predominantly in Oslo, the capital of Norway. Islamophobia has become a globally influential issue, and even welfare states like Norway have not remained immune to its effects. As a result, Norway has also been impacted by this global phenomenon. Following the September 11, 2001, terrorist attacks, anti-Muslim sentiments became more visible in Norway, with certain websites, NGOs, and politicians openly portraying Muslims as a potential threat to democracy. In this context, anti-Muslim and anti-immigrant sentiments began to strengthen in the country. The far-right “Progress Party” (Fremskrittspartiet) capitalized on this atmosphere, increasing its votes significantly and becoming the second-largest party in the Norwegian parliament. The aftermath of 9/11 created a dangerous precedent that, a decade later, would fuel the deadly ideology of Anders Behring Breivik, who carried out a terrorist attack in Norway driven by Islamophobic motives. For a certain period, Breivik was affiliated with the Progress Party’s youth wing, which suggests that the party’s nationalist and exclusionary discourse played a formative role in shaping his extremist worldview. Although Breivik eventually distanced himself from the party, considering it too weak for his radical goals, the ideological foundations laid by the party served as a cornerstone in constructing his lethal mindset. The main objective of this study is to identify how Muslims, who are members of mosque associations and religious organizations in Oslo, perceive and experience Islamophobia. A quantitative research method with a survey design was employed. The study sample consists of Muslim individuals affiliated with mosque associations operating in Oslo. Data were collected using the “Perceived Islamophobia Scale,” originally developed by Kunst et al. and adapted into Turkish by Kılıç and Acar under the title “Adaptation, Validity, and Reliability Study of the Perceived Islamophobia Scale.” Findings indicate that participants’ overall perception of Islamophobia is at a moderate level. While the dimensions of Islamization fear and general fear are also moderate, the influence of media is perceived at a high level. Participants emphasized the impact of media most strongly. Negative media representations of Muslims appear to be influential, particularly among women and individuals aged 31–45, who reported higher levels of Islamization fear. Therefore, the study underlines the responsibility of the media, the importance of education, and the need to raise social awareness in combating Islamophobia. It recommends the criminalization of Islamophobic discourse and the development of relevant state policies. Moreover, it emphasizes that Norway must address this issue at the level of official state policy.